Relationship between various physiological determinants of endurance performance in elite triathletes - Triska, C.; Ernst, J.; Soukup, C.; Scharner, M.; Powolny, V.; Mathy, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The apex of the fat oxidation curve (FATmax) as well as maximal fat oxidation rate (MFO) serve as indicators for metabolic health and performance [1]. Among others, peak oxygen uptake (VO2peak) and gross efficiency (GE) also represent key determinants for endurance performance [2]. A relationship of these parameters is debatable and there is a lack of data in elite athletes and therefore, the aim of this work was to assess a potential relationship between parameters of fat oxidation and VO2peak as well as GE in a cohort of elite triathletes. METHODS: Fourteen male elite triathletes (stature 1.83 ± 0.06 m, body mass 71.2 ± 5.5 kg, incremental peak power output: 5.4 ± 0.2 W/kg) were recruited for this study. Participants performed a graded exercise test on a cycle ergometer (Cyclus2, RBM electronics, Germany) where respiratory gases were measured continuously (MetaMax 3B-R2, Cortex Biophysik GmbH, Leipzig, Germany). The test commenced at 80 W and load was increased by 40 W every 4 min. VO2 and carbon dioxide (VCO2) data were used to calculate fat oxidation according to [3] and the highest measured value for fat oxidation was accepted as FATmax [4]. FATmax was expressed relative to VO2peak. GE was calculated using VO2 and VCO2 data obtained from the last minute of the stage that corresponded to FATmax intensity. Pearson moment correlation was used to assess the strength of any relationship between FATmax (%VO2peak) and VO2max (mL/min/kg), between FATmax (%VO2peak) and GE, and between VO2peak (mL/min/kg) and GE. Standard errors of the estimates were calculated for significant correlations and significance was accepted at p < 0.050. RESULTS: Mean ± SD were 62.4 ± 6.5%, 21.4 ± 1.0%, and 68 ± 5 mL/min/kg for FATmax (%VO2peak), GE, and VO2peak, respectively. Significant correlations were found between FATmax and VO2max (p = 0.016; r = -0.631, SEE = ±5.2%) and VO2peak and GE (p = 0.010; r = -0.664; SEE = ±0.8%), but not between FATmax and GE (p = 0.106; r = 0.451). CONCLUSION: Present results indicate a strong negative relationship between FATmax intensity and VO2peak, but merely a moderate and non-significant relationship between FATmax intensity and GE. This suggests that a higher aerobic power is associated with a lower relative intensity of maximal fat oxidation, but no association exists between GE and FATmax. Data therefore confirms an inverse relation between VO2peak and the intensity where the highest fat oxidation occurs. This inverse relationship, however, questions the notion of the non-trainability of FATmax. In accordance with previous published work in cyclists a strong negative relationship was found between GE and VO2peak in a cohort of elite triathletes [5].